Os projetos formativos como meio de desenvolvimento de competências socioemocionais e espirituais-religiosas: uma abordagem na perspectiva da formação integral - Longhi, Marcio (Universidade do Vale do Rio dos Sinos, 2022)
The present research aims at investigating the issues of integral formation and of educational management. The scope of the research is the Espaço MAGIS Anchieta, where we intend to study the Service of Religious, Spiritual and Pastoral Guidance (SOREP) formative project, regarding the social-emotional and spiritual-religious skills development among educators, from the perspective of an integral formation according to the Society of Jesus. The theoretical framework of this research addresses education from the point of view of language and knowledge fragmentation. The concept of skills and abilities is developed as a foundation for the analysis of the BNCC, as well as to broaden the social-emotional and spiritual-religious dimensions, which are necessary for an integral education in this research's standpoint. We proposed a qualitative research methodology, using a semi-structured interview as a data collection tool. The data analysis was developed through the content analysis technique. The data analysis was developed through four categories, two directly associated with the theme of integral formation and the development of social-emotional and spiritual-religious competencies, providing indicators of the project in terms of its integral formative potential, as well as of the knowledge acquired by the participants regarding these competencies, thereby allowing the comparison between the research findings in relation to the formative concepts of the Society of Jesus. The other two categories account for the educational management dimension of the project, highlighting the methodologies and formative processes, the structure, and the organization of Espaço MAGIS Anchieta. The findings obtained in these two categories, brought together, highlighted the project's strengths and weaknesses, and its challenges and opportunities, thereby supporting its qualification. Furthermore, the data analysis has allowed the design of a set of indicators that, based on the BSC perspectives, can qualify the training and educational management processes related to Espaço MAGIS Anchieta.
Keywords: Formação integral; Competências socioemocionais; Competências espirituais-religiosas; Gestão educacional; Integral formation; Social-emotional competencies; Spiritual-religious competencies; Educational management; ACCNPQ::Ciências Humanas::Educação